Dexamethasone Protects Against Radiation-induced Loss of Auditory Hair Cells In Vitro. Issue 10 (December 2015) - Dinh, Christine; Chen, Si; Padgett, Kyle; Dinh, John; Telischi, Fred; Elsayyad, Nagy; Johnson, Perry; Angeli, Simon; Bas, Esperanza; Goncalves, Stefania; Eshraghi, Adrien; Van De Water, Thomas
Abstract : Hypothesis: Dexamethasone (DXM) protects against radiation-induced loss of auditory hair cells (HCs) in rat organ of Corti (OC) explants by reducing levels of oxidative stress and apoptosis. Background: Radiation-induced sensorineural hearing loss (HL) is progressive, dose-dependent, and irreversible. Currently, there are no preventative therapeutic modalities for radiation-induced HL. DXM is a synthetic steroid that can potentially target many of the pathways involved in radiation-induced ototoxicity. Methods: Whole OC explants were dissected from 3-day-old rat cochleae exposed to specific dosages of single-fraction radiation (0, 2, 5, 10, or 20 Gy), were either untreated or treated with DXM (75, 150, 300 μg/mL), and then cultured for 48 or 96 hours. Confocal microscopy for oxidative stress (CellRox, 48 h) and apoptosis (TUNEL assay, 96 h) and fluorescent microscopy for viable HC counts (fluorescein isothiocyanate-phalloidin, 96 h) were performed. Analysis of variance and Tukey post hoc testing were used for statistical analysis. Results: Radiation exposure initiated dose-dependent losses of inner and outer HCs, predominantly in the basal turns of the OC explants. DXM protected against radiation-induced HC losses in a dose-dependent manner. DXM significantly reduced levels of oxidative stress and apoptosis in radiation-injured OC explants ( p  < 0.001). Conclusions: Radiation-initiated HC losses were dose-dependent in OC explants. DXM treatment protected explant HCs against radiation-initiated losses by decreasing the levels of oxidative stress and apoptosis. DXM may potentially be a therapeutic modality for preventing radiation-induced HL; further in vivo studies are necessary.